Wetsuit technology & speed - Woolley, H. (1999)
This article provides information that can help you understand wetsuit technology in greater depth and make you a more discerning consumer. The article deals with: 1. Materials & Buoyancy 2. Material Thickness & Buoyancy 3. Material Thickness & Body Position 4. Materials: Thickness & Flexibility 5. Materials Buoyancy & Stretch 6. Surface Coating 7. Design & Fit 8. Type of Material